Moderating role of insecure attachment styles in the relationship between spiritual compatibility with spiritual growth and psychological distress in university students who experienced emotional failure - Abbas Amanelahi; Safa Safaei Moghadam; Manochehr Taghipour (فصلنامه علمی- پژوهشی اصول بهداشت روانی, 2022)
Introduction: This study aimed to determine mediating role of insecure attachment styles on relationship between spiritual compatibility with spiritual growth and psychological distress in university students who experienced emotional failure. Materials and Methods: The statistical community of this study consisted of all male students in Ahvaz universities who experienced emotional failure in their relationships with girls. Among them, 200 men were selected by the purposeful sampling method. The research instruments included spiritual compatibility questionnaire, spiritual assessment inventory, revised attachment styles questionnaire, and psychological distress questionnaire. Data analyzed through SPSS-21, regression, and simple correlation method. Results: The results showed that there is a significant relation between spiritual compatibility with spiritual growth (P= 0.001, r= 0.58) and also there is a negative relation between spiritual compatibility and psychological distress (P= 0.001, r= -0.17). Also the results of mediating regression showed that insecure attachment style mediate the relation between spiritual compatibility with spiritual growth (P= 0.05, β= -1.12) but insecure attachment style does not mediate the relation between spiritual compatibility and psychological distress (P= 0.96, β= 0.03). Conclusion: According to the results, spiritual compatibility plays a role in spiritual growth and mental health. Insecure attachment style has a moderating role in the relationship between spiritual compatibility and spiritual growth.